Dual RNA Sequencing Reveals the Genome-Wide Expression Profiles During the Compatible and Incompatible Interactions Between Solanum tuberosum and Phytophthora infestans - Li, Honghao; Hu, Rongping; Fan, Zhonghan; Chen, Qinghua; Jiang, Yusong; Huang, Weizao; Tao, Xiang (Frontiers in Plant Science, 2022)
Late blight, caused by Phytophthora infestans, is a devastating plant disease. P. infestans genome encodes hundreds of effectors, complicating the interaction between the pathogen and its host, and making it difficult to understand the interaction mechanisms. In this study, the late blight resistant potato cultivar Ziyun No.1 and the susceptible cultivar Favorita were infected with P. infestans isolate SCPZ16-3-1 to investigate the global expression profiles during the compatible and incompatible interactions using dual RNA-Seq. Most of the expressed RXLR effector genes were suppressed during the first 24 h of infection, but up-regulated after 24 h. Moreover, P. infestans induced more specially expressed genes (SEGs), including RXLR effectors and cell wall-degrading enzyme (CWDEs) encoding genes, in the compatible interaction. The resistant potato activated a set of biotic stimulus responses and phenylpropanoid biosynthesis SEGs, including kirola-like protein, nucleotide-binding site-leucine rich repeat (NBS-LRR), disease resistance, and kinase genes. Conversely, the susceptible potato cultivar up-regulated more kinase, pathogenesis-related genes than the resistant cultivar. This study is the first to characterize the compatible and incompatible interactions between P. infestans and different potato cultivars and provides the genome-wide expression profiles for RXLR effector, CWDEs, NBS-LRR protein, and kinase encoding genes.